A collaborative approach for solving the university course timetabling problem - Bazilio, Carlos (2019)
This work proposes a collaborative approach for solving the university course timetabling problem (UCTP). A prototype was developed and used for a computer science course at the Federal Fluminense University in Brazil. The main idea is that students, professors, and course coordinators contribute collaboratively to course timetabling through an app. These contributions employ heuristics, which is responsible for timetabling to improve the solution to the problem. Results and future works are described herein.